Pengembangan Media Pembelajaran Video Tutorial Interaktif menggunakan Aplikasi Camtasia Studio dan Macromedia Flash - Wirasasmita, Rasyid Hardi; Putra, Yupi Kuspandi (Universitas Hamzanwadi, 2017)
This research is an R & D (research and development) research that is an interactive tutorial video CD-based learning model in visual programming language courses that are more seen, with and practiced. That is, is the development of a model of teaching materials in other forms, which are complementary to existing teaching materials. This application presents material interactively with animation, audio, video and is equipped with an evaluation in the form of practice questions using the Camtasia Studio and Macromedia Flash applications. The results that will be achieved from the making of this learning media is that students can understand the subjects of visual programming language and find out the quality of the interactive video CD tutorial based on the assessment of media experts, material experts and learning. The results of a feasibility assessment of video tutorials learning media for visual programming language subjects are: (1) the percentage score of material expert assessment was 81.25%; (2) the percentage score of media expert assessment was 84.5%; (3) the percentage score of student response was 84.83%. Based on the results of the assessment and responses obtained, we can conclude that this instructional media of video tutorials on programming language of visual delphi is feasible to be used and developed.